Urticaria: An update on pathophysiology, diagnosis, and management - Chieh Chen; Da-Ming Liao (Tungs’ Medical Journal)
Urticaria is a relatively common clinical skin disorder, and the condition is an inflammatory allergic immune response in the skin mucosa which increases the permeability of the subcutaneous capillaries. Localized, treatment-resistant skin edema is a characteristic symptom of urticaria. The activation of mast cells located in the dermal layer of the skin and consequent release of histamines is thought to be the primary cause of the pathology of urticaria. The broad definition of urticaria also includes contact urticaria and measles vasculitis, and recent studies have shown that almost half of patients with persistent spontaneous urticaria have mast cell receptor autoimmunity. These patients need immediate attention, because they may also have other severe medical or surgical conditions. The low number of studies on chronic urticaria means that thorough serological investigation of patients is not typically advised clinically. There is presently no scientific evidence connecting malignancy or persistent infections to urticaria.